Pharmacology in Midwifery - Donnellan-Fernandez, Roslyn; Bazargan, Maryam; Davison, Clare; Gray, Michelle; Small, Kirsten (ELSEVIER, 2025)
Written by highly respected experts in both pharmacology and midwifery, the textbook takes the reader through essential information about drugs and their therapeutic effects. It then explores pharmacology in the midwifery scope of practice, considering pregnancy, labour, birth, the postpartum period and neonatal care, both for normal and low risk pregnancies and women with complex needs.This book is a useful foundation text for midwifery students as well as for practising midwives wishing to refresh or augment their skills as prescribers.